Preparation and Characteristics of Kluwak Shell Carbon Adsorbent - Yuliani HR; Dian Ranggina; Miftahul Janna; Zulham Nurul Fadhila; Arif Budiman (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2024)
Kluwak shell carbon (KTK) is a biomass with potential as an adsorbent, containing cellulose, hemicellulose, lignin, and fixed carbon at a content of 92.15%. However, the current utilization of KTK in adsorbing free fatty acids and methylene blue is limited and can be improved through thermal activation at a range of temperatures. The study aims to investigate the impact of activation temperature on CEC by examining the adsorption capacity of methylene blue solution, iodine solution, and surface area. Activation was carried out for 2 hours at temperatures ranging from 500 to 900 C on Kluwak shell carbon. The adsorbent performance of the activated KTKAT was initially tested using methylene solution with a concentration of 50 ppm, a volume of 50 ml, and 0.15 grams of KTKAT. The solution was placed in an orbit shaker for 90 minutes and filtered. The absorbance of the filtrate adsorption results was measured at a wavelength of 662 nm using UV VIS. For the second test, 50 ml of 0.1 N Iodine and 0.5 g KTKAT were stirred for 15 minutes and then centrifuged for approximately 15 minutes. A volume of 10 ml of the resulting iodine solution adsorption filtrate was titrated with 0.1 N Sodium Thiosulfate. The surface area was determined using the BET method. The concentration (ppm) of methylene blue solution was determined by converting the absorbance measurement using the standard curve equation. The iodine number was determined by titrating the iodine adsorption filtrate with sodium thiosulfate (ml). These data show that there is an obvious correlation between activation temperature and methylene blue absorbance, iodine number, and surface area. At 800Â°C, the methylene blue adsorption is 12.41 mg/g, the iodine number is 875.61 mg/g, and the surface area is 561.404 mÂ²/g.